2013
DOI: 10.1177/0269216313491796
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care for advanced renal disease:  A summary of the evidence and future direction

Abstract: Background: Patients with end-stage kidney disease can have a significant symptom burden with complex co-morbidities. Compounding this is the choice between dialysis and conservative management. Need for supportive and palliative care: For individuals with end-stage kidney disease, palliative care can provide support with symptom management, advance care planning and psychological support and education for both patients and their families. Optimum management may be achieved through collaboration between renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 35 publications
1
45
0
2
Order By: Relevance
“…A few studies have addressed symptoms in elderly dialysis or nondialysis patients with CKD and have shown a high symptom burden in all cases, often analogous to the burden carried by patients with cancer (8,36). O'Connor and Kumar (27) found only six studies of symptom burden or QOL in patients managed without dialysis, with a mean 7-17 symptoms, similar to our mean of 12.…”
Section: Symptom Control and Qolsupporting
confidence: 68%
“…A few studies have addressed symptoms in elderly dialysis or nondialysis patients with CKD and have shown a high symptom burden in all cases, often analogous to the burden carried by patients with cancer (8,36). O'Connor and Kumar (27) found only six studies of symptom burden or QOL in patients managed without dialysis, with a mean 7-17 symptoms, similar to our mean of 12.…”
Section: Symptom Control and Qolsupporting
confidence: 68%
“…(8,42,43) Some patients suggested that the PCP might be the best person to lead ACP discussions. Preferences discussed with the PCP could then be shared with the dialysis team in an integrated care model.…”
Section: Discussionmentioning
confidence: 99%
“…25 The UK Renal Registry does not currently collect data on patients who choose conservative management or who have stable CKD stage V. However, a number of smaller studies have compared outcomes for these patients. 6,21,[27][28][29][30][31][32][33][34] Taken as a whole, patients who choose to dialyse do, generally, live longer that those who choose conservative management, although it does vary quite significantly from study to study, depending in part on definition of conservative management used. However, they also spend much more time in hospital (including dialysis attendances) 28 and frequently report that they are so exhausted after a dialysis session that they cannot even manage to prepare a meal.…”
Section: -24mentioning
confidence: 99%